2015
DOI: 10.1177/1533317514566114
|View full text |Cite
|
Sign up to set email alerts
|

ApoE Type 4 Allele Affects Cognitive Function of Aged Population in Tianjin City, China

Abstract: Apolipoprotein E type 4 allele (ApoE∊4) is known as a risk gene for the late-onset Alzheimer's disease, and the relationship between ApoE∊4 and cognitive function of the elderly people has drawn the attention of the scientists. In this study, we investigated the relationship between ApoE∊4 and the cognitive function of the old people. A total of 156 old people were investigated, of whom 31 were ApoE∊4 carriers. The ApoE∊4 primarily influenced the global cognitive function, perceptual speed, and work memory. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…In a Korean population, APOE genotype was not associated with age-related cognitive decline [ 23 ] (though it was associated with Alzheimer’s disease risk [ 24 ]). By contrast, studies of Chinese elders found that APOE was associated with age-related cognitive decline [ 25 ], as well as cross-sectional cognitive ability [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a Korean population, APOE genotype was not associated with age-related cognitive decline [ 23 ] (though it was associated with Alzheimer’s disease risk [ 24 ]). By contrast, studies of Chinese elders found that APOE was associated with age-related cognitive decline [ 25 ], as well as cross-sectional cognitive ability [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, the APOE ε4 allele is not associated with the MMSE score in Chinese older adults. Although some studies form western countries (e.g., Northern Europe) have found APOE ε4-related decline in global cognitive function [35,36], the population-based study failed to observe a signi cant association of APOE ε4 allele with MMSE score in Chinese older adults [37]. Of note, compared to the proportion of people carrying APOE ε4 allele in the Nordic population (around 25-30%), the proportion in our study is relatively low (14.9%), and only 1.4% carried the homozygote 4 allele.…”
Section: Associations Of Apoe ε4 Allele Tomm40 G Allele With Cognitimentioning
confidence: 88%
“…E4 has been related most strongly to global cognition as well as to specific cognitive domains like episodic memory (Marioni et al, 2016;Small et al, 2004), executive function, and processing speed (Luciano et al, 2009;Marioni et al, 2016;Wisdom et al, 2011). Other studies have also linked e4 status to worse working memory, visuospatial attention, perceptual speed, and visual memory in older nondemented subjects (Caselli et al, 2004;Greenwood, Sunderland, Friz, & Parasuraman, 2000;Lim et al, 2012;Sun et al, 2015). Nevertheless, reports remain inconsistent in this matter (Caselli et al, 2004;Devanand et al, 2005;Nilsson, Nyberg, & Ba¨ckman, 2002;Small et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…APOE e4 allele frequency is also significantly higher in other neurodegenerative diseases, including Lewy body dementia (Tsuang et al, 2013), frontotemporal degeneration (Rubino et al, 2013), Parkinson's disease with dementia (Tsuang et al, 2013), and vascular dementia (Yin et al, 2012). Being a major lipid transporter in the brain, APOE among others impacts neuronal plasticity and repair, and the e4 isoform is believed to negatively affect these processes (Arendt et al, 1997;Li et al, 2015;Mauch et al, 2001;Teter et al, 2002;White, Nicoll, Roses, & Horsburgh, 2001). Moreover, it may also be related to cognitive impairment through brain damage provoked by atherosclerosis (Davignon, Cohn, Mabile, & Bernier, 1999;Mahley, Weisgraber, & Huang, 2009).…”
Section: Introductionmentioning
confidence: 99%